THE INFLUENCE OF FINANCIAL CONFIDENCE, HERDING BIAS, AND CONFIRMATION BIAS ON INVESTMENT DECISIONS IN GENERATION Z IN JAKARTA - Adiputra, I Gede; Nathaerwin , Nathaerwin (Graduate Program of Universitas Tarumanagara, 2024)
Interest in investing in the capital market for young investors is increasing. This is reflected in the increasing number of young investors in the capital market. Internet and digital technology have become part of today's society in all aspects. Technological developments in the financial services industry are referred to as Fintech (Financial Technology). Fintech is present starting from as a means of payment, E-Wallet, digital bank, to investment provider brokers. The purpose of this study is to examine and analyse the factors that influence Financial Confidence, Herding Bias, and Confirmation Bias on Generation Z's Investment Decision in Jakarta. The sample in the study were investors born between 1995-2010 called Generation Z and residing in Jakarta. The purposive sampling method was used to collect 205 respondents through Google Forms shared online on social media. The research data was analysed with a structural equation system using SmartPLS.3.2.9 software. The results showed, Financial confidence has a significant effect on investment decision making, Herding Bias has a significant effect on investment decision making, Confirmation bias has no effect on investment decision making.